Electroactive Ultra-Thin rGO-Enriched FeMoO4 Nanotubes and MnO2 Nanorods as Electrodes for High-Performance All-Solid-State Asymmetric Supercapacitors - Kugalur Shanmugam Ranjith; Ganji Seeta Rama Raju; Nilesh R. Chodankar; Seyed Majid Ghoreishian; Cheol Hwan Kwak; Yun Suk Huh; Young-Kyu Han (Nanomaterials, 2020)
A flexible asymmetric supercapacitor (ASC) with high electrochemical performance was constructed using reduced graphene oxide (rGO)-wrapped redox-active metal oxide-based negative and positive electrodes. Thin layered rGO functionality on the positive and the negative electrode surfaces has promoted the feasible surface-active sites and enhances the electrochemical response with a wide operating voltage window. Herein we report the controlled growth of rGO-wrapped tubular FeMoO4 nanofibers (NFs) via electrospinning followed by surface functionalization as a negative electrode. The tubular structure offers the ultrathin-layer decoration of rGO inside and outside of the tubular walls with uniform wrapping. The rGO-wrapped tubular FeMoO4 NF electrode exhibited a high specific capacitance of 135.2 F g−1 in Na2SO4 neutral electrolyte with an excellent rate capability and cycling stability (96.45% in 5000 cycles) at high current density. Meanwhile, the hydrothermally synthesized binder-free rGO/MnO2 nanorods on carbon cloth (rGO-MnO2@CC) were selected as cathode materials due to their high capacitance and high conductivity. Moreover, the ASC device was fabricated using rGO-wrapped FeMoO4 on carbon cloth (rGO-FeMoO4@CC) as the negative electrode and rGO-MnO2@CC as the positive electrode (rGO-FeMoO4@CC/rGO-MnO2@CC). The rationally designed ASC device delivered an excellent energy density of 38.8 W h kg−1 with a wide operating voltage window of 0.0−1.8 V. The hybrid ASC showed excellent cycling stability of 93.37% capacitance retention for 5000 cycles. Thus, the developed rGO-wrapped FeMoO4 nanotubes and MnO2 nanorods are promising hybrid electrode materials for the development of wide-potential ASCs with high energy and power density.